The Missing (Revolution Studios and Image Entertainment, 2003)
The Missing is the story of Maggie Gilkeson (Cate Blanchett), a young woman raising her two daughters in an isolated and lawless wilderness. When her oldest daughter (Evan Rachel Wood) is kidnapped by a psychopathic killer with mystical powers (Eric Schweig), Maggie is forced to re-unite with her long estranged father (Tommy Lee Jones) to rescue her. The killer and his brutal cult of desperados have kidnapped several other teenage girls, leaving a trail of death and horror across the desolate landscape of the American Southwest.
Directors: Ron Howard Writers: Ken Kaufman, Thomas Eidson Producers: Aldric La'Auli Porter, Brian Grazer, Daniel Ostroff, Kathleen McGill, Louisa Velis
Tommy Lee Jones, Cate Blanchett, Evan Rachel Wood, Jenna Boyd, Aaron Eckhart